Mengidentifikasi kinerja manajerial dalam meningkatkan nilai rumah sakit tipe d di Provinsi Lampung - Euis Mufahamah (Penerbit Goodwood, 2020)
Purpose: This study aims to analyze managerial performance in increasing the value or ranking of an organization as seen from the influence of total quality management, performance measurement systems, reward systems and organizational culture in type D hospitals in Lampung Province. Research methodology: Based on online hospital data there are 18 type D hospitals in Lampung Province. Using nonprobability sampling techniques, so that 90 samples were obtained through questionnaires. And data analysis techniques with partial least square (PLS) using the SmartPLS 3.0 application. Results: The results of the analysis concluded that total quality management has a significant effect on performance measurement systems and organizational culture has a significant effect on managerial performance. While the reward system, performance measurement system and total quality management through performance measurement systems do not have a significant effect on managerial performance. Limitations: The limitation of the research is only the variable total quality management, performance measurement systems, reward systems, organizational culture and managerial performance. And the object of research is only in one particular type and location. Contribution: The results of this study are expected to provide information, thoughts and references for future researchers, as well as evaluating and driving managerial performance in increasing the value of type D hospitals that are still low. So that the provision of excellent health services especially for people who are far from the city center is well facilitated. Keywords: Total quality management, Performance measurement systems, Reward systems, Organizational culture, Managerial performance